FORMING OF ALGORITHMIC REASONING STYLE AT FUTURE TEACHERS OF MATHEMATICS WITH THE HELP OF MATHEMAICAL EDUCATIONAL SOFTWARE - V. Berman; N. Lvova (Kherson State University, 2010)
Methodical aspects of using of educational mathematical software designed in Research institute of Kherson state university on practical training in methodic of mathematics for future teachers of mathematics are considered. The main goal is forming of algorithmic reasoning style.